A Synthetic Interaction between CDC20 and RAD4 in Saccharomyces cerevisiae upon UV Irradiation. (23rd February 2014) - Connors, Bernadette; Rochelle, Lauren; Roberts, Asela; Howard, Graham
Abstract : Regulation of DNA repair can be achieved through ubiquitin-mediated degradation of transiently induced proteins. In Saccharomyces cerevisiae, Rad4 is involved in damage recognition during nucleotide excision repair (NER) and, in conjunction with Rad23, recruits other proteins to the site of damage. We identified a synthetic interaction upon UV exposure between Rad4 and Cdc20, a protein that modulates the activity of the anaphase promoting complex (APC/C), a multisubunit E3 ubiquitin ligase complex. The moderately UV sensitive Δ rad4 strain became highly sensitive when cdc20-1 was present, and was rescued by overexpression of CDC20 . The double mutant is also deficient in elicting RNR3-lacZ transcription upon exposure to UV irradiation or 4-NQO compared with the Δ rad4 single mutant. We demonstrate that the Δ rad4 / cdc20-1 double mutant is defective in double strand break repair by way of a plasmid end-joining assay, indicating that Rad4 acts to ensure that damaged DNA is repaired via a Cdc20-mediated mechanism. This study is the first to present evidence that Cdc20 may play a role in the degradation of proteins involved in nucleotide excision repair.